The Effect of Graphene on the Mechanical Properties of High Density Polyethylene (HDPE)/Zinc Borate Polymer Composite - TAŞDEMİR, MÜNİR; ULUTAŞ, ELİF (My University, 2023)
In this study; A composite was produced by adding 5% zinc borate and different amounts of graphene powders into high density polyethylene (HDPE). Five different groups were obtained by mixing the materials forming the composite in a twin screw extruder and standard test samples were produced using an injection machine. Tensile, hardness and impact tests were performed to determine the mechanical values. In addition, photographs were taken with scanning electron microscopy (SEM) to determine the distributions of zinc borate and graphene. As a result of the analysis, with the addition of zinc borate and graphene powder in HDPE; It was determined that the modulus of elasticity, tensile strength, breaking strength and hardness values increased, while the values of impact strength, elongation at break and elongation at break decreased. As a result of SEM examination, it was determined that zinc borate and graphene powders were homogeneously dispersed.

Bu çalışmada; yüksek yoğunluklu polietilenin (YYPE) mekanik özelliklerinin çinko borat ve grafen ilavesi ile geliştirilmesi hedeflenmiş olup yüksek yoğunluklu polietilen içerisine %5 oranında çinko borat ve farklı oranlarda grafen tozları katılarak bir kompozit üretilmiştir. Kompoziti oluşturan malzemeler çift vidalı ekstrüzyon makinesinde karıştırılarak beş farklı grup elde edilmiştir ve enjeksiyon makinası kullanılarak standart test numuneleri üretilmiştir. Mekanik değerleri belirlemek için çekme, sertlik ve darbe testleri yapılmıştır. Ayrıca çinko borat ve grafenin dağılımlarını belirlemek için taramalı elektron mikroskobisi (SEM) ile fotoğrafları çekilmiştir. Analizler sonucunda YYPE içerisinde çinko borat ve grafen toz ilavesiyle; elastiklik modülü, çekme mukavemeti, kopma mukavemeti ve sertlik değerlerinin arttığı diğer taraftan darbe mukavemeti kopma uzaması ve kopma uzaması değerlerinin ise düştüğü tespit edilmiştir. SEM inceleme sonucu çinko borat ve grafen tozlarının homojen dağıldığı tespit edilmiştir.
Yüksek Yoğunluklu Polietin (YYPE)/Çinko Borat Polimer Kompozitinin Mekanik Özelliklerine Grafenin Etkisi
Keywords: High density polyethylene; Zinc borate; Graphene; Mechanical properties; Composite material; Yüksek yoğunluklu polietilen; Çinko borat; Grafen; Mekanik özellikler; Kompozit malzeme